1959
DOI: 10.1002/j.1537-2197.1959.tb07072.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Ovule and Megagametophyte in Saxifraga Hieracifolia

Abstract: WIGGINS, IRA 1. (Stanford U., Stanford, Calif.) Development of the ovule and megagameto· phyte in Saxifraga hieracifolia. Amer, Jour. Bot. 46(10) : 692-697. Illus. 1059.-Buds of Saxifraga hieracijolia collected in the vicinity of Point Barrow, Alaska, fixed, sectioned, and stained by standard methods, revealed that the archesporial cell in the ovule of this species is hypodermal and gives rise to the megaspore mother cell and a small number of parietal cells. Occasionally 2 megaspore mother cells occur within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

1959
1959
1982
1982

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…crassifolia, by Schiirhoff (1925) in S. decipiens x granulata, by Chapman (1933) in S. virginiensis, by Harmsen (1939) in S. stellaris var. comosa, by Wiggins (1959) in S. hieracifolia and by Saxena (1964a) in S. diversifolia. In addition, there are some papers in which development is described incompletely.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…crassifolia, by Schiirhoff (1925) in S. decipiens x granulata, by Chapman (1933) in S. virginiensis, by Harmsen (1939) in S. stellaris var. comosa, by Wiggins (1959) in S. hieracifolia and by Saxena (1964a) in S. diversifolia. In addition, there are some papers in which development is described incompletely.…”
mentioning
confidence: 96%
“…In the genus Saxifraga, the most representative herbaceous genus of this family, however, both unitegmic and bitegmic conditions have been reported. Chapman (1933), Harmsen (1939), and Wiggins (1959) reported the occurrence of the unitegmic ovules in Saxifraga virginiensis, S. stellaris, and S. hieracifolia, respectively, while Juel (1907) and Saxena (1964a) reported that the ovules of S. granulata and S. diversifolia had two integuments, and, judging from the figures in Pace (1912), S. ligulata and S. crassifolia also have bitegmic ovules, though not clearly mentioned in the manuscript. Chapman (1933) and Harmsen (1939) did not discuss the relationships between bitegmic and unitegmic conditions within the genus Saxifraga.…”
mentioning
confidence: 99%
See 3 more Smart Citations